The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1124/dmd.115.065011
|View full text |Cite
|
Sign up to set email alerts
|

Further Characterization of the Metabolism of Desloratadine and Its Cytochrome P450 and UDP-glucuronosyltransferase Inhibition Potential: Identification of Desloratadine as a Relatively Selective UGT2B10 Inhibitor

Abstract: Desloratadine (Clarinex), the major active metabolite of loratadine (Claritin), is a nonsedating antihistamine used for the treatment of seasonal allergies and hives. Previously we reported that the formation of 3-hydroxydesloratadine, the major human metabolite of desloratadine, involves three sequential reactions, namely N-glucuronidation by UGT2B10 followed by 3-hydroxylation by CYP2C8 followed by deconjugation (rapid, nonenzymatic hydrolysis of the N-glucuronide). In this study we assessed the perpetrator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 31 publications
(51 reference statements)
4
19
0
1
Order By: Relevance
“…3 demonstrate that UGT2B10 is responsible for .90% of cotinine N-glucuronidation by HLM, making this compound a convenient, readily available UGT2B10 substrate probe. Moreover, compared with many other UGT enzyme-selective substrate probes, cotinine does not bind to BSA Consistent with the recent report of Kazmi et al (2015b), desloratadine was shown to be a moderately selective inhibitor of UGT2B10 (Fig. 2B).…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…3 demonstrate that UGT2B10 is responsible for .90% of cotinine N-glucuronidation by HLM, making this compound a convenient, readily available UGT2B10 substrate probe. Moreover, compared with many other UGT enzyme-selective substrate probes, cotinine does not bind to BSA Consistent with the recent report of Kazmi et al (2015b), desloratadine was shown to be a moderately selective inhibitor of UGT2B10 (Fig. 2B).…”
Section: Discussionsupporting
confidence: 71%
“…2B; (Supplemental Table 2). In general, the inhibition observed in this study for desloratadine (10 mM) is in good agreement to that reported by Kazmi et al (2015b) for hepatically expressed UGT enzymes, except UGT2B4, which was not investigated by these authors.…”
supporting
confidence: 80%
See 3 more Smart Citations